Demographic and clinical characteristics of older people with multimorbidity accessing primary healthcare in Malawi: A cross-sectional study - Duncan Kwaitana; James Jafali; Maya Jane Bates; Dorothee van Breevoort; Thomas Mildestvedt; Eivind Meland; Eric Umar (Journal of Multimorbidity and Comorbidity)
Background Multimorbidity is a growing global concern, affecting patient outcomes and healthcare costs. In low- and middle-income countries, data on multimorbidity in primary care beyond prevalence is limited. Our study explored the demographic and clinical characteristics of multimorbidity among older people attending primary health care in Malawi. Methods We conducted a cross-sectional analysis on medical records from 15,009 older patients aged ≥50 years across three hospitals in Malawi (one tertiary, two district). Data from 2019-2021 was analyzed using R statistical software to examine patterns of multimorbidity (two or more chronic conditions). Outcome estimates were adjusted for sex, age, location, and year of clinic visit. Results The overall prevalence of multimorbidity, defined across 17 recorded chronic conditions, was 19.6%. Among the 2,941 cases of multimorbidity, 2,708 (92.0%) involved two chronic conditions, while 233 (8.0%) involved three. While most conditions increased steadily in prevalence with age, diabetes followed a different pattern, with higher prevalence among individuals aged 50–59 years (53.9%) and 60–69 years (52.4%) compared to those 70 years and older (40.3%). After adjusting for clinic visit year, gender, and study location, individuals aged 70 years and older were significantly less likely to have multimorbidity compared to those aged 50–59 years (AOR = 0.57, 95% CI: 0.52–0.62, p < 0.001). Conclusion The study revealed a wide range of multimorbidity combinations among older people attending primary health care. Strategies to address multimorbidity in older people should include efforts to identify other, less common clusters of chronic conditions.